The Impact of Individual Differences, Types of Model and Social Settings on Block Building Performance among Chinese Preschoolers - Tian, Mi; Deng, Zhu; Meng, Zhaokun; Li, Rui; Zhang, Zhiyi; Qi, Wenhui; Wang, Rui; Yin, Tingting; Ji, Menghui (Frontiers in Psychology, 2018)
Children’s block building performances are used as indicators of other abilities in multiple domains. In the current study, we examined individual differences, types of model and social settings as influences on children’s block building performance. Chinese preschoolers (N = 180) participated in a block building activity in a natural setting, and performance was assessed with multiple measures in order to identify a range of specific skills. Using scores generated across these measures, three dependent variables were analyzed: block building skills, structural balance and structural features. An overall MANOVA showed that there were significant main effects of gender and grade level across most measures. Types of model showed no significant effect in children’s block building. There was a significant main effect of social settings on structural features, with the best performance in the 5-member group, followed by individual and then the 10-member block building. These findings suggest that boys performed better than girls in block building activity. Block building performance increased significantly from first to second year of preschool, but not from second to third. The preschoolers created more representational constructions when presented with a model made of wooden rather than with a picture. There was partial evidence that children performed better when working with peers in a small group than when working alone or working in a large group. It is suggested that future study should examine other modalities rather than the visual one, diversify the samples and adopt a longitudinal investigation.